PENGARUH METODE BERMAIN PASIR TERHADAP KEMAMPUAN MENGENAL BENTUK-BENTUK GEOMETRI PADA ANAK USIA 4-5 TAHUN DI RA KURNIA PEKANBARU - Khusna, Nikmatul; Zulkifli N, Zulkifli N; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absrtak: The background of the researchers conducting this research is the lack of children in recognizing geometric shapes, the lack of children in showing geometric forms, to an unqualified children in pointing geometric forms in accordance with its name, less inability to predict the next sequence by using 3 pattern. This study aims to determine the effect of sand play method to recognize the ability of geometric shapes children aged 4-5 years in RA Kurnia Pekanbaru. The population and sample of this research is children aged 4-5 years with 15 children. The technique of collecting data obtained by observation. The collection of data by means of pre-test and post-test to post-test administration before the experiment. The analysis technique used in this study is to test the wilxocon. The results were obtained information that the value of Z obtained at -3.282 with p value of 0.001 where the value is less than the critical limit of 0.05 studies, so the decision hypothesis is Ha Ho accepted and rejected. Which means there are significant or sand play method to recognize the ability of geometric shapes children aged 4-5 years in RA Kurnia Pekanbaru. Whereas, the influence method of play sand on the ability recognize geometric shapes children aged 4-5 years in Pekanbaru Kurnia RA is 4.6%. Which means that the rest of 95.4% ability to recognize geometric shapes children is influenced by other factors.Keywords : The ability to recognize geometric shapes, methods of play sand